Caracterización y propuesta técnica de la acuicultura en los cantones de jipijapa y montecristi de la provincia de Manabí - Centeno, Jorge (2010)
The cantons, Jipijapa and Montecristi, belonging to the province of Manabí, are world renowned for its handicrafts made by hand, however, these counties are within its territory an oceanfront area, where they carried traditional aquaculture crops and breeding projects non-traditional aquaculture, an area known as Boca of Puerto Cayo, Canton Jipijapa , provided millions of shrimp larvae and wild shrimp nauplii in the eighties, developed a proposed mariculture, and there is also a fish-breeding project in the mountainous area , while in the urban area of the canton Montecristi, some laboratories operated and we found a groundwater area a few miles from the coast, in which 2 inland shrimp farms are operating. Our study's main aim is to describe the evolution of aquaculture in the area, identify areas of culture, the current state of the aquaculture industry, and the potential of these